Faktor-Faktor yang Memengaruhi Behavioral Intention Penggunaan Chatbot Shopee pada Gen Z di DKI Jakarta - Hipnu Maulana; Mohamad Rizan; Ryna Parlyna (Indonesia Economic Journal, 2026)
This study aims to analyze the factors that influence Generation Z's behavioral intention in using Shopee chatbots as artificial intelligence-based customer service on e-commerce platforms. The variables tested in this study include performance expectancy, social influence, and trust in behavioral intention. This study uses a quantitative approach with a survey method. Data was collected from Generation Z respondents residing in DKI Jakarta who had used the Shopee chatbot. The sampling technique used was purposive sampling. Data was collected through an online questionnaire. The data analysis technique used was Structural Equation Modeling (SEM) with a Partial Least Squares (PLS) approach to test the relationship between variables in the research model. The results showed that performance expectancy and social influence had a positive and significant effect on trust. Furthermore, trust and social influence were found to have a positive and significant effect on behavioral intention to use the Shopee chatbot. However, performance expectancy did not show a significant direct effect on behavioral intention. Furthermore, the test results showed that trust mediates the effect of performance expectancy and social influence on behavioral intention. These findings indicate that user trust plays an important role in driving Generation Z's intention to use Shopee's chatbot. This study recommends that e-commerce companies, especially Shopee, focus more on developing chatbots that improve reliability, security, and response quality in order to build user trust and increase the intention to use chatbot services on an ongoing basis.